2008
DOI: 10.3732/ajb.0800092
|View full text |Cite
|
Sign up to set email alerts
|

Root anatomy, morphology, and longevity among root orders in Vaccinium corymbosum (Ericaceae)

Abstract: Understanding root processes at the whole-plant or ecosystem scales requires an accounting of the range of functions within a root system. Studying root traits based on their branching order can be a powerful approach to understanding this complex system. The current study examined the highly branched root system of the ericoid plant, Vaccinium corymbosum L. (highbush blueberry) by classifying its root orders with a modified version of the morphometric approach similar to that used in hydrology for stream clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
197
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 54 publications
7
197
1
1
Order By: Relevance
“…These results reinforce Brundrett (2002), who suggested that plant species with less root cortical volume sacrifice the capacity for arbuscular mycorrhizal associations, and Valenzuela-Estrada et al (2008), who observed this in Vaccinium spp., where roots with greater radial growth and reduced specific root length had less mycorrhizal colonization.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results reinforce Brundrett (2002), who suggested that plant species with less root cortical volume sacrifice the capacity for arbuscular mycorrhizal associations, and Valenzuela-Estrada et al (2008), who observed this in Vaccinium spp., where roots with greater radial growth and reduced specific root length had less mycorrhizal colonization.…”
Section: Discussionsupporting
confidence: 78%
“…Because SimRoot does not explicitly consider beneficial aspects of secondary root growth, such as axial water transport (Valenzuela-Estrada et al, 2008), mechanical support of the shoot, or resistance to herbivores and pathogens (Eissenstat, 1992;Valenzuela-Estrada et al, 2008), reduced secondary growth is unconditionally beneficial for improving root length and P acquisition in silico. In vivo, secondary growth is a constitutive characteristic of dicot roots, and the inverse relationship between secondary growth and P acquisition predicted by the model is only present under P stress.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the fine root life span of a shrub species increases with increasing root order (Valenzuela-Estrada et al 2008). For some shrub species, the turnover rate of the first two order roots could be twice as high as that of the third order roots (Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fitter (1982) introduced a morphometric approach to describe these architectural features based on topological models which rely on Strahler's stream ordering system (Fig. S1;Strahler 1957;Pregitzer et al 2002;Valenzuela-Estrada et al 2008). The most distal roots in a branching system are first order roots; the node from which two first order roots branch marks the location of a second order root, and so on (Strahler 1957;Guo et al 2004).…”
Section: Role Of Branching Order In Fine Root Decompositionmentioning
confidence: 99%
“…This variability reflects the arbitrary nature of fine root designations or, less often, differences in diameter among plant species (Fitter 1996). Recent studies have shown that fine roots occupying different positions within a branching system (root orders), vary predictably in structure, function and thus rates of turnover and decomposition for several different long-lived perennial species (Pregitzer 2002;Wang et al 2006;Guo et al 2004Guo et al , 2008aGuo et al , 2008bValenzuela-Estrada et al 2008;Fan and Guo 2010;Goebel et al 2011;Xiong et al 2013). For the purpose of this review, the most distal roots in a branching network are defined as first order roots.…”
Section: Introductionmentioning
confidence: 99%